The microstructural, textural, and mechanical effects of high-pressure torsion processing on Mg alloys: A review - Yan, Zhaoming; Zhu, Jiaxuan; Zhang, Zhimin; Wang, Qiang; Xue, Yong (Frontiers in Materials, 2022)
Magnesium (Mg) alloys attract great attention in the fields of aerospace, defense technology and automobile owning to the advantages of low density, high specific strength/specific stiffness, good damping performance and excellent electromagnetic shielding performance. However, the low strength and poor ductility limitedslimits the further application. Severe plastic deformation is considered to be the most promising way to fabricate the ultrafine-grained Mg alloys and improve the mechanical properties significantly, high pressure torsion (HPT) is one of the most effective techniques. Thus, this paper reveals the microstructure, texture and mechanical properties of Mg alloys processed by HPT. The effects of deformation parameters, such as processing temperature, turns, applied pressure and rotation speed, on the grain refinement and secondary phases wereare discussed. The texture evolution considering the influence of many intrinsic and extrinsic factors such as the accumulative strain and alloy elements composition wereare detailed summarized. Subsequently, the significant enhancement of mechanical properties, and the resultant strengthening mechanisms and their contribution to strength wereare further reviewed. Based on the advantages of HPT on grain refinement and structure modification, several novel processes based on the principle of HPT wereare proposed by researchers to spread its industrial application.